2004
DOI: 10.1038/ni1047
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin imposes T cell unresponsiveness through targeted proteolysis of signaling proteins

Abstract: Sustained calcium signaling induces a state of anergy or antigen unresponsiveness in T cells, mediated through calcineurin and the transcription factor NFAT. We show here that Ca(2+)-induced anergy is a multistep program that is implemented at least partly through proteolytic degradation of specific signaling proteins. Calcineurin increased mRNA and protein of the E3 ubiquitin ligases Itch, Cbl-b and GRAIL and induced expression of Tsg101, the ubiquitin-binding component of the ESCRT-1 endosomal sorting comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
565
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(600 citation statements)
references
References 52 publications
31
565
3
1
Order By: Relevance
“…In accordance with early studies showing Cbl-b upregulation in anergized T cells, Cbl-b À/À T cells are resistant to ionomycin-induced anergy [34,40]. Under anergic conditions, Cbl-b upregulation correlates with PLCg1 and PKCy ubiquitylation and an ensuing calcium mobilization defect, suggesting these two molecules may be crucial targets for Cbl-b anergic functions [34,40].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tosupporting
confidence: 87%
See 2 more Smart Citations
“…In accordance with early studies showing Cbl-b upregulation in anergized T cells, Cbl-b À/À T cells are resistant to ionomycin-induced anergy [34,40]. Under anergic conditions, Cbl-b upregulation correlates with PLCg1 and PKCy ubiquitylation and an ensuing calcium mobilization defect, suggesting these two molecules may be crucial targets for Cbl-b anergic functions [34,40].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tosupporting
confidence: 87%
“…Beside its role in T-cell differentiation, Itch has also been implicated in the regulation of T-cell tolerance. As in the case of Cbl-b, Itch is upregulated in vitro under anergizing stimuli [40]. In accordance, Itch À/À Th2 cells are resistant to ionomycin-induced anergy as well as high doses of tolerizing antigen in a mouse model for asthmatic airway inflammation [51].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tomentioning
confidence: 68%
See 1 more Smart Citation
“…Our data that both Egr-2 and Egr-3 are upregulated by ionomycin alone and that their induction is not dependent upon MAP-kinase activation support this hypothesis. Of interest, it has been proposed that the upregulation of the E3 ligases represents an important component of NF-AT-induced inhibition [30]. Previously, we have shown that the E3 ligase Cbl-b is decreased in T cells from Egr-3 null mice and increased with the overexpression of Egr-3.…”
Section: Discussionmentioning
confidence: 80%
“…79 The NFAT target genes include the RING E3 ligases Cbl-b and GRAIL, as well as the HECT E3 Itch and Nedd4. 80 TCR/CD28 restimulation of 'TCR-only' treated T cells promotes the execution of the anergic gene program. Just like in naïve T cells upon a first encounter with an antigen, primary SMAC formation is not affected in anergic T cells, but the SMACs are highly unstable and the synapse collapses within minutes after engagement.…”
Section: Cd28 Sets the Threshold: The Role Of Ubiquitin Ligasesmentioning
confidence: 99%